Megabenthic invertebrate diversity in Mediterranean trawlable soft bottoms: a synthesis of current knowledge - STAMOULI, CATERINA; ZENETOS, ARGYRO; KALLIANIOTIS, ARGYRIOS; VOULTSIADOU, ELENI (Mediterranean Marine Science, 2022)
Mediterranean bottom trawling is generally characterised by a highly diversified mixed catch, composed of fish, cephalopods, crustaceans, and other megabenthic invertebrates. Although management of Mediterranean trawling requires a multispecies approach on a community basis, this does not seem to be the case in the relevant literature. Herein, we present an extensive review of the existing knowledge on megabenthic invertebrate communities, focusing on the trawlable bottoms. A total of 207 publications from 1930 to the early 2021 was collected and classified into seven research areas. Research effort on soft bottom megabenthic invertebrates of trawlable grounds was higher for the Western Mediterranean and the depth zone of 50-200 m. Overall, 1,797 taxa were reported belonging to different taxonomic groups, the most diverse of which were Mollusca, Crustacea, Polychaeta, and Porifera. Among the reported taxa, 43 species are alien to the Mediterranean Sea, and 42 are included in the lists of threatened/ endangered and protected species under the Barcelona and Bern Conventions. The Western Mediterranean and the Aegean Sea were the ecoregions with the highest number of megabenthic invertebrate species reported from trawlable grounds. All Mediterranean ecoregions were grouped according to their megabenthic fauna at a similarity level of 27%. The present work compiles the known scattered information, highlights knowledge gaps, and underlines the need for time series data on the megabenthic communities of the Mediterranean fishing grounds.